2021
DOI: 10.1021/acsami.0c22654
|View full text |Cite
|
Sign up to set email alerts
|

BiVO4/Cs2PtI6 Vacancy-Ordered Halide Perovskite Heterojunction for Panchromatic Light Harvesting and Enhanced Charge Separation in Photoelectrochemical Water Oxidation

Abstract: Photoelectrochemical water oxidation is a challenging reaction in solar water splitting due to the parasitic recombination process, sluggish catalytic activity, and electrode stability. Oxide semiconductors are stable in an aqueous medium but show huge charge carrier recombination. Creation of a heterojunction is found to be effective for extracting the photogenerated electrons/holes before they recombine to the ground state. In this work, we created a heterojunction of BiVO4 with vacancy-ordered halide perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 67 publications
(117 reference statements)
1
23
0
Order By: Relevance
“…[38] In our previous reports, we have also shown that varying the A-site from Cs 2 PtI 6 (r Cs ¼ 1.88 Å, r Pt ¼ 0.625 Å) to Rb 2 PtI 6 (r Rb ¼ 1.72 Å) or varying B-site to Cs 2 SnI 6 (r Sn ¼ 0.69 Å) provide similar diffraction pattern but with a shift in peak to higher 2θ value for smaller A or B-site element. [23,25] The diffraction patterns of chloride-and bromide-based compounds were also found to be matching with the Joint Committee on Powder Diffraction Standards data (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…[38] In our previous reports, we have also shown that varying the A-site from Cs 2 PtI 6 (r Cs ¼ 1.88 Å, r Pt ¼ 0.625 Å) to Rb 2 PtI 6 (r Rb ¼ 1.72 Å) or varying B-site to Cs 2 SnI 6 (r Sn ¼ 0.69 Å) provide similar diffraction pattern but with a shift in peak to higher 2θ value for smaller A or B-site element. [23,25] The diffraction patterns of chloride-and bromide-based compounds were also found to be matching with the Joint Committee on Powder Diffraction Standards data (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 55%
“…In our previous work, we have shown that Cs 2 PtI 6 is stable even in harsh acidic or basic conditions and can be employed as a photoanode for PEC water oxidation. [ 23,25 ] Similarly, a recent report on Cs 2 PtBr 6 nanocrystals also showed good PEC performance displaying a current density of 0.335 mAcm −2 . [ 31 ] These reports on PEC cells employed intrinsic materials without mixed halides or metal‐sites and have already shown excellent performance.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…For photocatalysis applications, good photocatalysis for water splitting or CO 2 reduction techniques should meet the requirement of (1) a suitable bandgap for absorption of the solar spectrum; (2) immediate electron-hole separation of the material; (3) high stability in aqueous medium against corrosion; (4) the redox potential of the material is suitable for H 2 generation and CO 2 reduction. Cs 2 PtI 6 is also used as a photoanode for the photoelectrochemical (PEC) water oxidation process [ 15 , 16 ] due to its stability even in an acidic or bases environment. In Jayanthan et al.…”
Section: Introductionmentioning
confidence: 99%